Pregnancy outcome in patient who had first trimester bleeding in previous pregnancy: a prospective study - M., Faswila; R., Ramya N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Patient who had history of spontaneous abortion in her previous pregnancy is associated with adverse outcome in her present pregnancy. Methods: A total 63 pregnant women attending OPD and admitted in department of obstetrics and gynecology, Yenepoya Medical College, from April 2017 to September 2017, considered and outcome were studied. Results: Out of 63 patient’s majority (57.1%) of patients belong to the age group 21-29 year. Anemia was found to be very severe in 4.3%, severe in 10% and moderate in 30% patients. Maximum patients (45.7%) were with history of previous one abortion followed by previous two abortions (38.6%). The final outcomes were term livebirth 47 (74.3%), abortion 9 (14.3%), preterm delivery 5 (8.6%), and stillbirth 2 (2.8%) caesarean section (23.3%) for various indications. 19.23% had term PROM, 9.09% had PPROM, 5.76% had term IUGR, 3.84% term IUD, preterm IUD accounts for 9.09% and still birth accounted for about 1.92% which was term, pre-eclampsia accounted for 4.76%, malpresentation for 7.93%, total 3 cases of antepartum hemorrhage out of which placenta previa accounts for about 3.1% and abruption for 1.58%, manual removal of placenta 4.7% and low birth weight 7.6%. Conclusions: Previous history of spontaneous abortion is associated with adverse pregnancy outcome. There is increased risk of abortion, preterm delivery, need for caesarean sections and fetal loss which can be reduced by booking and giving antenatal care.